2015
DOI: 10.1016/j.bmcl.2014.10.091
|View full text |Cite|
|
Sign up to set email alerts
|

Metal-assisted synthesis of unsymmetrical magnolol and honokiol analogs and their biological assessment as GABAA receptor ligands

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…For subsequent biological studies, a modular synthetic strategy was developed towards structural analogs of 3 and 6 based on cross coupling chemistry [ 28 ] (Fig. 4 ).…”
Section: Selected Findings Of the Dnti Projectmentioning
confidence: 99%
“…For subsequent biological studies, a modular synthetic strategy was developed towards structural analogs of 3 and 6 based on cross coupling chemistry [ 28 ] (Fig. 4 ).…”
Section: Selected Findings Of the Dnti Projectmentioning
confidence: 99%
“…Magnolol ( I ) is a lignan found in the bark of the plant Magnolia officinalis which has been used in traditional Chinese medicine as potential anti-inflammatory, anti-cancer, and neuromodulatory agent as well as a lead structure for synthetic derivatives. 7 , 8 We previously demonstrated that magnonol ( I ) is a partial PPARγ agonist. 9 However, magnolol ( I ) was found to activate RXRα as well.…”
Section: Introductionmentioning
confidence: 99%
“…This work focused on the ambition to further exploit the biaryl-system of magnolol and honokiol in order to create selective PPARγ ligands 12 with no concomitant effect on RXRα. We made use of the recent report on the co-crystallization of magnolol with the ligand binding domains of RXRα and PPARγ 10 .…”
Section: Introductionmentioning
confidence: 99%